Nematicity in LaFeAsO single crystals studied by elastoresistance, high-resolution thermal expansion, and shear modulus measurements - Hong, Xiaochen; Sauerland, S.; Wang, L.; Scaravaggi, F.; Wolter, A. U. B.; Kappenberger, R.; Aswartham, S.; Wurmehl, S.; Sykora, S.; Caglieris, F.; Büchner, B.; Hess, C.; et al. (Physical review, 2025)
Nematicity in LaFeAsO single crystals is studied by means of high-resolution thermal expansion, shear modulus, and elastoresistivity measurements. A softening of the shear modulus 𝐶66 towards the structural phase transition at 𝑇S is observed. In addition, a similar Curie-Weiss-like divergence of the nematic susceptibilities is found in the temperature dependence of both 𝜒sh and 𝜒er, which are deduced from the shear modulus (sh) and the elastoresistivity (er) studies, respectively. These observations provide evidence for an electronic origin of nematicity in LaFeAsO. The characteristic energy of the coupling between the lattice and the electronic degrees of freedom is deduced to ≈30K. The comparison to corresponding measurements on BaFe2⁢As2 single crystals reveals a very similar temperature dependence of the shear modulus but yields contrasting results for 𝜒er : In BaFe2⁢As2, 𝜒er diverges similarly as the uncoupled nematicity deduced from the shear modulus data as it is expected from the underlying Landau theory. In contrast, the Weiss temperatures of 𝜒er and 𝜒sh are significantly different in LaFeAsO. This difference is at odds with the commonly anticipated theories of resistivity anisotropy and electronic nematicity in iron pnictides.